A note on the chemical composition, intake and digestion of striga hermonthica herbage by sheep - Hess, D.E.; Fernández Rivera, S. (Wiley, 2000)
Striga hermonthica causes serious crop yield losses in West Africa. Hand pulling, an effective method for the reduction of light infestations, might be encouraged if farmers could use this weed as livestock feed. This study evaluated the chemical composition and the voluntary intake and digestion of S. hermonthica herbage by sheep. Crude protein (g kg -1 dry matter (d.m.)) was 184 in the whole plant, 230 in the leaf and 87 in the stem. Ash content varied from 183 to 253 g kg d.m.-1. The concentration of neutral and acid detergent fibre and lignin in whole pot-grown plants was 364, 278 and 127 g kg d.m.-1 respectively. The digestibility of dry and organic (o.m.) matter was 493 and 657 g kg -1, respectively, and intake of digestible o.m. was 27.1 g kg W-0.75. The relatively high N and P levels in S. hermonthica warrant further evaluation in terms of its potential use as a source of protein or for compost. Its use as a feed appears to be limited by the high ash content and possibly by anti-nutritional effects on animals. These effects should be further investigated before recommending its use for this purpose.